Constitutional Complaints and the Constitutionality of Pro Justitia Measures: A Comparative Analysis of Indonesia, Germany, and South Korea - Ivan Zairani Lisi; Nur Aripkah; I Kadek Sudiarsana; Nadia Nabela; Faiqah Nur Azizah (Universitas Islam Negeri Raden Intan Lampung, 2025)
In practice, pretrial hearings in Indonesia often fail to be an effective instrument for protecting the rights of suspects and victims in the Pro Justitia process. Many cases show that the imbalance between law enforcement officials' authority and individual rights remains an unresolved. This situation differs from that in Germany and South Korea, where constitutional complaints have become an important instrument in the constitutional system for controlling and correcting state actions that violate citizens' constitutional rights, including within the criminal justice system. This study examines the extent to which the absence of a constitutional complaint mechanism in the Indonesian criminal justice system affects the protection of citizens' constitutional rights. Using a normative legal research method, with a statute, conceptual, and comparative approach, this study found that Indonesia has yet to implement a constitutional complaint mechanism as a corrective measure against state actions that violate citizens' constitutional rights. Preliminary hearings still have limitations in accommodating constitutional rights in criminal proceedings. The absence of this mechanism creates a void in the constitutional protection system in the judicial process in Indonesia as a whole. The implementation of constitutional complaints should be considered to strengthen the protection of constitutional rights and ensure the implementation of the Pro Justitia process in line with the principles of the rule of law